Pengembangan LKPD Digital Berbasis STEM Untuk Meningkatkan Literasi Numerasi Dan Sains Peserta Didik - Fikri Ahmad Kamal; Bambang Subali; Budi Astuti; Ani Rusilowati; Arif Widiyatmoko (Postgraduate, University of Mataram, 2024)
As a result of interviews with class VIII science teachers at SMP Negeri 15 Semarang, information was obtained that most of the teaching materials used in the Archimedes law material were still in the form of printed teaching materials (student worksheet, modules and textbooks), PPTs and learning videos. The available teaching materials are not yet fully electronic, thus preventing students from accessing learning without time and space limitations. This causes students' numeracy and science literacy skills to be low. The aim of this research is to determine the characteristics of STEM-based digital student worksheet, test the feasibility of STEM-based student worksheet, analyze the increase in numeracy and science literacy after using STEM-based digital student worksheet. This research uses research and development methods. This method can be used to develop teaching materials, namely digital student worksheet. The design of the digital student worksheet development research is based on the Thiagarajan 4D model which includes the definition stage, design stage, development stage and dissemination stage. The research results show that this digital student worksheet is designed to be interactive, containing elements such as links, moving images, audio and video which can increase students' numeracy and science literacy; the results of the digital student worksheet feasibility assessment obtained feasible criteria with a result score of 0.85 (media) and 0.84 (material). The results of this research show that there is an increase in the N-Gain value.